STUDI AERODINAMIKA KENDARAAN LISTRIK VU-EV DENGAN PENDEKATAN COMPUTATIONAL FLUID DYNAMICS (CFD) - Imanuel Timotius Arifin; Ferly Isnomo Abdi; Aji Nugroho; Lailatus Sa’diyah Yuniar Arifianti; Chaska Akhila Ade Diandra (Universitas Negeri Surabaya, 2025)
This research analyzes the aerodynamic characteristics of the VU-EV electric vehicle using Computational Fluid Dynamics (CFD) simulation. The study evaluates airflow patterns, pressure distribution, and wake formation at three speeds (20 km/h, 25 km/h, and 30 km/h), aiming to enhance the aerodynamic efficiency and performance of a six-passenger electric golf car equipped with solar panels.The simulation results indicate that higher speeds result in more turbulent airflow, greater pressure differentials between the front and rear, and increased aerodynamic drag. For future studies, improvements in body design—especially at the rear—and the addition of aerodynamic devices are recommended to minimize drag, alongside experimental validation to ensure simulation accuracy and wider applicability for the development of sustainable vehicles.